Nutritional evaluation of spent and uninoculated mushroom substrate of Pleurotus ostreatus grown on cassava peels and sawdust - Samuel Echezonachi Okere; Frank Ojiako; Chinyerum Gloria Ikechi-Nwogu; Chinwendu Augustina Ojiaku; Nkechi Udochukwu Ezechike (International Journal of Advances in Applied Sciences, 2023)
This study aims to evaluate the role of edible fungi in the biodegradation of mushroom substrate by comparing the mineral and proximate composition of a pasteurized substrate before inoculation (BI) with the spent mushroom substrate (SMS) of Pleurotus ostreatus cultivated on cassava peels and sawdust. The experiment was conducted at the Federal University of Technology, Owerri, Imo State Nigeria. The treatment for this investigation comprised different levels of wheat bran namely: T1 (C/N 17:0 in the control), T2 (C/N ratio 17:1), and T3 (C/N ratio 17:3). 2% lime was added to the substrate to stabilize the pH. The experiment was laid out in a completely randomized design (CRD) which was replicated three times. The mineral and proximate compositions were determined using standard procedures. The data generated were subjected to analysis of variance (ANOVA) at (p = 0.05). The result obtained from this investigation reviewed that the mineral composition before substrate inoculation was significantly higher than those obtained from the SMS which were in the range: of Na (0.10-0.17 mg/kg), Mg (0.25-0.40 mg/kg), Ash (1.56-2.65%), Ca (0.62-1.40 mg/kg), K (0.25-0.42 mg/kg), and P (0.11-0.44 mg/kg) while the proximate composition is in the range: dry matter (81.6-93.3%), N (0.18-0.31%), crude protein (CP) (1.13-1.94%), crude fiber (2.84-4.82%). This result revealed that significant quantities of the nutrients unlocked by Pleurotus ostreatus were assimilated into the mushroom fruit bodies. Therefore, Pleurotus ostreatus could be used to enrich cassava peels and sawdust substrates which can further be utilized in the formulation of livestock feeds. However, further studies are recommended especially in evaluating more nutritional indices of the substrate.